2018
DOI: 10.1590/s0004-2803.201800000-48
|View full text |Cite
|
Sign up to set email alerts
|

Are the Persistent Symptoms to Proton Pump Inhibitor Therapy Due to Refractory Gastroesophageal Reflux Disease or to Other Disorders?

Abstract: BACKGROUND: Gastroesophageal reflux disease (GERD) is a clinical condition that develops when the reflux of stomach contents causes troublesome symptoms and/or complications. Transient lower esophageal sphincter relaxation is the main pathophysiological mechanism of GERD. Symptoms and complications can be related to the reflux of gastric contents into the esophagus, oral cavity, larynx and/or the lung. Symptoms and other possible manifestations of GERD are heartburn, regurgitation, dysphagia, non-cardiac ches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
0
14
0
8
Order By: Relevance
“…Previous studies have shown that there is no significant difference in the total episodes of reflux determined by 24-hour pH monitoring in unresponsive patients after PPI treatment, and the total episodes of weak-acid and non-acid reflux in refractory GERD patients were significantly more than that in the control group. 42,43 In addition, only 5.0% of reflux symptoms were related with acid reflux, while 16.7% were related to non-acid reflux, suggesting most unresponsive GERD patients after PPI treatment are caused by non-acid reflux. 42,43 Unresponsiveness after PPI treatment in patients with GERD is also associated with poor compliance, psychiatric comorbidities, and functional gastrointestinal disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that there is no significant difference in the total episodes of reflux determined by 24-hour pH monitoring in unresponsive patients after PPI treatment, and the total episodes of weak-acid and non-acid reflux in refractory GERD patients were significantly more than that in the control group. 42,43 In addition, only 5.0% of reflux symptoms were related with acid reflux, while 16.7% were related to non-acid reflux, suggesting most unresponsive GERD patients after PPI treatment are caused by non-acid reflux. 42,43 Unresponsiveness after PPI treatment in patients with GERD is also associated with poor compliance, psychiatric comorbidities, and functional gastrointestinal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 In addition, only 5.0% of reflux symptoms were related with acid reflux, while 16.7% were related to non-acid reflux, suggesting most unresponsive GERD patients after PPI treatment are caused by non-acid reflux. 42,43 Unresponsiveness after PPI treatment in patients with GERD is also associated with poor compliance, psychiatric comorbidities, and functional gastrointestinal disorders. 44,45 After taking PPI, gastric acid secretion is reduced, and the pH in the stomach rises to 4.0 or higher, inhibiting the activation of pepsinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Their dosages range from 20 to 40 mg daily. PPI will cure the esophagitis up to 90%; 80% will recur within 1 year if treatment is stopped [14][15][16][17].…”
Section: Medicalmentioning
confidence: 99%
“…Gastroesophageal reflux disease (GERD) is a condition that is believed to occur due to dysfunction of the lower esophageal sphincter, which is responsible for preventing back flow of stomach contents into the esophagus 6 . This regurgitation of gastric juices into the esophagus, oropharyngeal and oral cavity lowers their pH 7 . In the esophagus, this can contribute to chronic inflammation, histological changes in the mucosal cells lining the distal esophagus, and increased risk for esophageal cancer 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%